Developing Arabic Language Teachers’ Competence and Performance through Teacher Profession Education - Ateng Ruhendi; Nanang Kosim (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2022)
This study aims to investigate the Arabic language teachers’ competence and performance who participated in PPG (Pendidikan Profesi Guru/ Teacher Profession Education) at LPTK (Lembaga Pendidik dan Tenaga Kependidikan/ Education Staff and Teacher College) UIN Syarif Hidayatullah Jakarta. The present study applied a qualitative approach and analytical descriptive method. Data were collected using observation techniques, interviews, questionnaires, and documentation. Data were analyzed through several steps: organizing data, translating data into units, synthesizing, analyzing, and making conclusions. The validity of the data was tested using the triangulation technique. The results showed that the Arabic language teachers’ level of competence before joining PPG was taken from their Initial Competency Test and their average academic test score was 62.53 (medium category). After they joined PPG, there was an increase in their competence and performance. Their gain can be seen from several indicators: discipline, dedication, motivation, work ethic. The average value of each indicator was 6.5%.